Analisis Pemanfaatan Media Sosial sebagai Media Penunjang Pembelajaran Agribisnis pada Mahasiswa Universitas Adzkia Padang - Ahmad Fachri; Juli Adevia; Nora Damayanti (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This study aims to examine the extent to which social media is utilized in agribusiness learning among students at Universitas Adzkia. A quantitative descriptive approach was employed, using a Likert scale-based questionnaire as the research instrument. The collected data were tabulated and classified into score percentages to determine the category of social media utilization. The research was conducted from June to July 2024 using a census method, involving all 38 students enrolled in the Agribusiness Study Program at Universitas Adzkia. The findings indicate that overall, the use of social media in agribusiness learning falls into the moderate category, with a score percentage of 55.76%. When broken down into agribusiness sub-systems, the results show that the use of social media in the agricultural input supply sub-system was 55.76%, in farming activities 56.14%, agricultural product processing 49.67%, marketing 44.08%, and agribusiness support services 47.20%. These results suggest that although social media has been used in the learning process, its utilization is still at a moderate level and not yet evenly distributed across all agribusiness sub-systems. This presents both opportunities and challenges for lecturers and educational institutions to develop more innovative, technology-based learning strategies. To enhance the effectiveness of agribusiness learning, it is recommended that lecturers actively encourage students to use social media in a productive manner. This could be implemented through the assignment of structured tasks that require the use of social media platforms for academic discussions, information searches, and the creation or sharing of relevant agribusiness content. Such efforts are expected to make social media not only a tool that enriches students' learning experiences but also a means to deepen their understanding of the dynamic and ever-evolving field of agribusiness. Ultimately, integrating social media into learning can support the development of digital competencies and practical insights among agribusiness students in higher education.